Good Governance Strategies in Building School Resilience : A Systematic Literature Review - Mulyana, Mulyana; Wasino, Wasino; Fakhruddin, Fakhruddin; Millah, Roihatul (Proceedings of International Conference on Science, Education, and Technology, 2025)
This governance framework is designed to strengthen school resilience. As the world grows increasingly complex and unstable, existing challenges are exacerbated and new ones emerge, including academic schedule disruptions, financial constraints, and sociocultural or environmental crises. A school's ability to endure challenges and adapt to changing conditions is arguably one of the most critical governance principles at this stage. We argue that a strong governance framework that prioritizes transparency, accountability, stakeholder participation, and leadership competence is key to fostering resilience. This conceptual paper examines organizational resilience alongside educational leadership to assess a school’s capacity for prevention, responsiveness, adaptability, and transformation when facing adversity. The article emphasizes key governance approaches such as stakeholder engagement, policy formulation, resource allocation, and the cultivation of an organizational culture that enables schools to withstand all stages of difficulty. The central premise is that promoting educational governance principles goes beyond mere administrative compliance and requires strategic planning to ensure educational institutions are proactive in addressing current issues while maintaining relevance for students and communities.